INOVASI PEMBELAJARAN PAI MELALUI ARTIFICIAL INTELLIGENCE (AI) - Syarif, Lailiya Rachmawati (Prodi Pendidikan Agama Islam, 2025)
This study explores the innovation of Islamic Religious Education (PAI) through the integration of Artificial Intelligence (AI) in the digital era. The rapid development of technology offers new opportunities to improve the effectiveness and engagement of PAI learning. Using a library research approach, the study analyzes various AI-based educational innovations, such as adaptive learning systems, interactive content, and AI-assisted teaching methods like chatbots and personalized learning recommendations. The results indicate that AI can significantly enhance student motivation, understanding, and efficiency in learning. However, challenges such as teacher readiness and ethical data concerns remain major obstacles. Therefore, continuous training and clear data policies are crucial for effective AI implementation in PAI.